PERLINDUNGAN HAK-HAK FUNDAMENTAL PEREMPUAN DALAM SITUASI KONFLIK DI INDONESIA (STUDI KASUS AMBON-MALUKU TAHUN 1999-2002) - Febrika Ganang Adista, Rizki Irfano Aditya, Dimas Trisuseno (GEMA, 2015)
This study aimed to analyze the compatibility between national law and international law regarding the protection of womenâs fundamental rights during conflict situations in Ambon and explain what law can be applied in Ambon conflict and also to describe the forms of womenâs protection in conflict situations.This legal research included in normative legal research with prescriptive paradigm. The type of legal material used is the primary legal materials and secondary legal materials. The technique of collecting the legal materials is literature reviews. The technique of analysis used in the study is interpretation method.The result of the study shows that there has been no correspondence between the Indonesian national laws and international law, the laws applied are the Indonesian national law and international human rights law which has been adopted by Indonesiaâs laws and regulations. The forms of protection for the womenâs fundamental rights are the establishment of special regulations for women, the construction of infrastructure and facilities for women and the penalties enforcement for the violators.Â